Going out into the World in Dictatorship’s Times: The Grandmothers of the Plaza de Mayo and Transnational Advocacy Networks for Human Rights (1977-1983) (Quinto Sol, 2020)
In this article we analyze the interaction between the Grandmothers of the Plaza de Mayo and the transnational advocacy networks for human rights during the years of the last military dictatorship in Argentina. In the first place, we analyze the main characteristics and actors of these networks and reconstruct the process and the modalities of insertion of the Grandmothers of the Plaza de Mayo in them. Secondly, we inquire into the repertoire of action and the different forms of collaboration of international human rights organizations with the Argentinian group. Finally, we discuss the medium and long-term effects that these relationships had for the Grandmothers of the Plaza de Mayo, both for the dissemination of its cause and for its consolidation as an independent organization.
Keywords: dictatorship; Grandmothers of the Plaza de Mayo; transnational networks; human rights